Transcription Dynamics and DNA Methylation Responses to Growth Modification - Kris A. Christensen; Étienne Collette; Danielle Perley; Dionne Sakhrani; Annette F. Muttray; Rosalind A. Leggatt; Carlo A. Biagi; Ben F. Koop; Robert H. Devlin (Marine Biotechnology, 2025)
To better understand how gene transcription is controlled under different physiological and environmental conditions, we assessed transcription and methylation responses in a vertebrate system (salmon) where growth can be manipulated in response to growth hormone transgenesis or under satiated, feed-deprived, and re-fed experimental conditions. In both transgenic and non-transgenic liver tissue, methylation of gene promoters was negatively associated with transcription at all measured times. However, the changes in promoter methylation among time-points did not generally correlate with changes in gene transcription among treatments. The results from this study suggest that only a subset of genes are readily responsive to changes in promoter methylation for a given environmental shift such as feed-deprivation or a physiological shift such as growth hormone transgenesis (i.e., genotype-by-environment interactions). The present study also reveals the complexity of how one tissue responds to alterations in internal changes in physiology (growth modification by growth hormone transgenesis; genotype), external environmental conditions (food availability; environment), and their interactions (genotype-by-environment effects).

Rapidly Changing Range Limits in a Warming World: Critical Data Limitations and Knowledge Gaps for Advancing Understanding of Mangrove Range Dynamics in the Southeastern USA - Rémi Bardou; Michael J. Osland; Steven Scyphers; Christine Shepard; Karen E. Aerni; Jahson B. Alemu I; Robert Crimian; Richard H. Day; Nicholas M. Enwright; Laura C. Feher; Sarah L. Gibbs; Kiera O’Donnell; et al. (Estuaries and Coasts, 2023)
Climate change is altering species’ range limits and transforming ecosystems. For example, warming temperatures are leading to the range expansion of tropical, cold-sensitive species at the expense of their cold-tolerant counterparts. In some temperate and subtropical coastal wetlands, warming winters are enabling mangrove forest encroachment into salt marsh, which is a major regime shift that has significant ecological and societal ramifications. Here, we synthesized existing data and expert knowledge to assess the distribution of mangroves near rapidly changing range limits in the southeastern USA. We used expert elicitation to identify data limitations and highlight knowledge gaps for advancing understanding of past, current, and future range dynamics. Mangroves near poleward range limits are often shorter, wider, and more shrublike compared to their tropical counterparts that grow as tall forests in freeze-free, resource-rich environments. The northern range limits of mangroves in the southeastern USA are particularly dynamic and climate sensitive due to abundance of suitable coastal wetland habitat and the exposure of mangroves to winter temperature extremes that are much colder than comparable range limits on other continents. Thus, there is need for methodological refinements and improved spatiotemporal data regarding changes in mangrove structure and abundance near northern range limits in the southeastern USA. Advancing understanding of rapidly changing range limits is critical for foundation plant species such as mangroves, as it provides a basis for anticipating and preparing for the cascading effects of climate-induced species redistribution on ecosystems and the human communities that depend on their ecosystem services.

Sexually Dimorphic Growth Stimulation in a Strain of Growth Hormone Transgenic Coho Salmon (Oncorhynchus kisutch) - Michelle T. T. Chan; Annette Muttray; Dionne Sakhrani; Krista Woodward; Jin-Hyoung Kim; Kris A. Christensen; Ben F. Koop; Robert H. Devlin (Marine Biotechnology, 2021)
Growth hormone (GH) transgenic fish often exhibit remarkable transformations in growth rate and other phenotypes relative to wild-type. The 5750A transgenic coho salmon strain exhibits strong sexually dimorphic growth, with females possessing growth stimulation at a level typical of that seen for both sexes in other strains harbouring the same gene construct (e.g. M77), while males display a modest level of growth stimulation. GH mRNA levels were significantly higher in females than in males of the 5750A strain but equivalent in the M77 strain, indicating sex and transgene insertion locus altered transgene expression. We found that acute estradiol treatments did not influence GH expression in either strain (5750A and M77) or the transgene promoter (metallothionein-B), suggesting that estradiol level was not a significant factor influencing transgene activity. The feminization of XX and XY fish of the 5750A and M77 strains generated all-female groups and resulted in equalized growth of the two genetic sexes, suggesting that the presence of the Y chromosome was not directly capable of influencing the GH transgene–mediated growth in a physiological female conditions. These data suggest that the difference in growth rate seen between the sexes in the 5750A strain arises from non-estradiol-mediated sex influences on gene regulation at the transgene locus. This study shows how genetic factors and transgene insertion sites can influence transgene expression with significant consequent effects on phenotype.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Fluorescent protein transgenesis has varied effects on behaviour and cold tolerance in a tropical fish (Gymnocorymbus ternetzi): implications for risk assessment - Rosalind A. Leggatt; Robert H. Devlin (Fish Physiology and Biochemistry, 2020)

Can sex-specific consumption of prey be determined from DNA in predator scat? - Brittany S. Balbag; Austen C. Thomas; Robert H. Devlin; Dietmar Schwarz (Conservation Genetics Resources, 2019)

Velocity Curvature Index: a Novel Diagnostic Biomarker for Large Vessel Occlusion - Samuel G. Thorpe; Corey M. Thibeault; Seth J. Wilk; Michael O’Brien; Nicolas Canac; Mina Ranjbaran; Christian Devlin; Thomas Devlin; Robert B. Hamilton (Translational Stroke Research, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Effects of recombinant salmon type II growth hormone and bovine growth hormone on growth of coho salmon (Oncorhynchus kisutch) - Annette F. Muttray; Edward M. Donaldson; Robert H. Devlin (Fish Physiology and Biochemistry, 2019)

Effect of growth hormone overexpression on gastric evacuation rate in coho salmon - Jin-Hyoung Kim; Satid Chatchaiphan; Michelle T. Crown; Samantha L. White; Robert H. Devlin (Fish Physiology and Biochemistry, 2018)

Expression of Thiaminase in Zebrafish (Danio rerio) is Lethal and Has Implications for Use as a Biocontainment Strategy in Aquaculture and Invasive Species - Sandra Noble; Vishal Saxena; Marc Ekker; Robert Devlin (Marine Biotechnology, 2017)

Age and intraspecific diversity of resilient Acropora communities in Belize - Adele Irwin; Lisa Greer; Robert Humston; Meghann Devlin-Durante; Paul Cabe; Halard Lescinsky; Karl Wirth; H. Allen Curran; Iliana B. Baums (Coral Reefs, 2017)

Ultrafine Particulate Matter Increases Cardiac Ischemia/Reperfusion Injury via Mitochondrial Permeability Transition Pore - Nathan A. Holland; Chad R. Fraiser; Ruben C. Sloan; Robert B. Devlin; David A. Brown; Christopher J. Wingard (Cardiovascular Toxicology, 2017)

De Novo Transcriptome Characterization and Growth-Related Gene Expression Profiling of Diploid and Triploid Bighead Catfish (Clarias macrocephalus Günther, 1864) - Satid Chatchaiphan; Prapansak Srisapoome; Jin-Hyoung Kim; Robert H. Devlin; Uthairat Na-Nakorn (Marine Biotechnology, 2017)

Identification of SNPs associated with transgenic and sex phenotypes in coho salmon (Oncorhynchus kisutch) - Erin McClelland; Michelle Chan; Dionne Sakhrani; Robert Devlin (Conservation Genetics Resources, 2016)

Red and white Chinook salmon: genetic divergence and mate choice - Sarah J. Lehnert; Trevor E. Pitcher; Robert H. Devlin; Daniel D. Heath (Molecular Ecology, 2016)
Chinook salmon ( Oncorhynchus tshawytscha ) exhibit extreme differences in coloration of skin, eggs and flesh due to genetic polymorphisms affecting carotenoid deposition, where colour can range from white to bright red. A sympatric population of red and white Chinook salmon occurs in the Quesnel River, British Columbia, where frequencies of each phenotype are relatively equal. In our study, we examined evolutionary mechanisms responsible for the maintenance of the morphs, where we first tested whether morphs were reproductively isolated using microsatellite genotyping, and second, using breeding trials in seminatural spawning channels, we tested whether colour assortative mate choice could be operating to maintain the polymorphism in nature. Next, given extreme difference in carotenoid assimilation and the importance of carotenoids to immune function, we examined mate choice and selection between colour morphs at immune genes (major histocompatibility complex genes: MHC I‐A1 and MHC II ‐B1). In our study, red and white individuals were found to interbreed, and under seminatural conditions, some degree of colour assortative mate choice (71% of matings) was observed. We found significant genetic differences at both MHC genes between morphs, but no evidence of MHC II ‐B1‐based mate choice. White individuals were more heterozygous at MHC II ‐B1 compared with red individuals, and morphs showed significant allele frequency differences at MHC I‐A1. Although colour assortative mate choice is likely not a primary mechanism maintaining the polymorphisms in the population, our results suggest that selection is operating differentially at immune genes in red and white Chinook salmon, possibly due to differences in carotenoid utilization.

Food Shortage Causes Differential Effects on Body Composition and Tissue-Specific Gene Expression in Salmon Modified for Increased Growth Hormone Production - Jason Abernathy; Stéphane Panserat; Thomas Welker; Elisabeth Plagne-Juan; Dionne Sakhrani; David A. Higgs; Florence Audouin; Robert H. Devlin; Ken Overturf (Marine Biotechnology, 2015)

Air pollution and health: emerging information on susceptible populations - Marie S. O’Neill; Carrie V. Breton; Robert B. Devlin; Mark J. Utell (Air Quality, Atmosphere & Health, 2012)

Analysis of gene origin in the first adult returns to the Cultus sockeye salmon captive breeding program - Ruth E. Withler; Robert H. Devlin; Steve Latham; Chris C. Wood; K. Janine Supernault (Conservation Genetics, 2011)

Standing genetic variation and compensatory evolution in transgenic organisms: a growth-enhanced salmon simulation - Robert N. M. Ahrens; Robert H. Devlin (Transgenic Research, 2011)

Increased intrinsic growth rate is advantageous even under ecologically stressful conditions in coho salmon (Oncorhynchus kisutch) - L. Fredrik Sundström; Robert H. Devlin (Evolutionary Ecology, 2011)

Differential Cardiopulmonary Effects of Size-Fractionated Ambient Particulate Matter in Mice - Haiyan Tong; Wan-Yun Cheng; James M. Samet; M. Ian Gilmour; Robert B. Devlin (Cardiovascular Toxicology, 2010)

Metabolic engineering of novel ketocarotenoid production in carrot plants - Jayaraman Jayaraj; Robert Devlin; Zamir Punja (Transgenic Research, 2008)

Biochemical and molecular differences in diploid and triploid ocean-type chinook salmon (Oncorhynchus tshawytscha) smolts - J. Mark Shrimpton; Aurora M. C. Sentlinger; John W. Heath; Robert H. Devlin; Daniel D. Heath (Fish Physiology and Biochemistry, 2007)

The glutathione antioxidant system is enhanced in growth hormone transgenic coho salmon (Oncorhynchus kisutch) - Rosalind A. Leggatt; Colin J. Brauner; George K. Iwama; Robert H. Devlin (Journal of Comparative Physiology B, 2007)

Transgene constructs in coho salmon (Oncorhynchus kisutch) are repeated in a head-to-tail fashion and can be integrated adjacent to horizontally-transmitted parasite DNA - Mitchell Uh; Jaswinder Khattra; Robert H. Devlin (Transgenic Research, 2006)

Effects of 3,5,3′-triiodo-L-thyronine (T3) and 6-n-propyl-2-thiouracil (PTU) on growth of GH-transgenic coho salmon, Oncorhynchus kitsutch - Duk-Young Kang; Robert H. Devlin (Fish Physiology and Biochemistry, 2003)

Gill Morphometry in Growth Hormone Transgenic Pacific Coho Salmon, Onchorhynchus kisutch, Differs Markedly from that in GH Transgenic Atlantic Salmon - E. Don Stevens; Robert H. Devlin (Environmental Biology of Fishes, 2000)

Lack of direct immunosuppressive effects of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) on human peripheral blood lymphocyte subsets in vitro - Dagmar S. Lang; Susannne Becker; George C. Clark; Robert B. Devlin; Hillel S. Koren (Archives of Toxicology, 1994)